2012
DOI: 10.1371/journal.pone.0043754
|View full text |Cite
|
Sign up to set email alerts
|

Plasma HIV Viral Rebound following Protocol-Indicated Cessation of ART Commenced in Primary and Chronic HIV Infection

Abstract: ObjectivesThe magnitude of HIV viral rebound following ART cessation has consequences for clinical outcome and onward transmission. We compared plasma viral load (pVL) rebound after stopping ART initiated in primary (PHI) and chronic HIV infection (CHI).DesignTwo populations with protocol-indicated ART cessation from SPARTAC (PHI, n = 182) and SMART (CHI, n = 1450) trials.MethodsTime for pVL to reach pre-ART levels after stopping ART was assessed in PHI using survival analysis. Differences in pVL between PHI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 21 publications
4
40
0
Order By: Relevance
“…One previously published study with more limited participants also compared HIV rebound kinetics between those treated during acute vs. chronic HIV infection and support our findings that those treated during acute infection were more likely to have delayed viral rebound [33]. A second study also found that post-ATI viral loads were lower in those treated during acute infection [34]. Possible explanations for these findings include a more restricted HIV reservoir [35][36][37] and immune preservation in participants who initiate ART during early infection.…”
Section: Discussionsupporting
confidence: 88%
“…One previously published study with more limited participants also compared HIV rebound kinetics between those treated during acute vs. chronic HIV infection and support our findings that those treated during acute infection were more likely to have delayed viral rebound [33]. A second study also found that post-ATI viral loads were lower in those treated during acute infection [34]. Possible explanations for these findings include a more restricted HIV reservoir [35][36][37] and immune preservation in participants who initiate ART during early infection.…”
Section: Discussionsupporting
confidence: 88%
“…This form of therapy combines at least three drugs, each of which can target a unique step in the viral life cycle including reverse transcription, integration, proteolytic processing, and viral entry (3). However, treatment must be continued indefinitely because ART interruption leads to rapid viremic rebound (4,5), and attempts at treatment intensification by additional drugs have not improved viremic control (6,7). Moreover, therapy is associated with a number of side effects and emergence of resistance, highlighting the need to explore new therapeutic modalities against HIV-1 (3).…”
Section: Cd4bs | Glycan | Gp160mentioning
confidence: 99%
“…However, the development of an effective vaccine or an alternative therapy remains the ideal solution since cART has several disadvantages. Adverse effects [1] , high costs of therapy, emergence of resistant viruses [2,3] and in particular, the fact that life-long continuous treatment is required [4][5][6] are just a few examples. Years of research pursuing an HIV-1 vaccine have shown how challenging this task continues to be, with even the most promising trials showing only marginal efficacy [7,8] .…”
Section: Introductionmentioning
confidence: 99%